Preparedness of Dentists to Manage Anxiety in Developmentally Disabled Patients - Maura B. Lynch; Lynn M. Tepper; Steven Chussid; Renuka Bijoor (Hindawi Limited, 2023)
Background. Recently, the National Council on Disability urged the Commission on Dental Accreditation to require more thorough training in the care of developmentally disabled patients. Curricula is early in its development and its' effectiveness is unknown. Objectives. The aim of this study was to determine if special needs dental education has had an impact on providers' professional behavior, practice characteristics, attitudes, and confidence when treating these patients and managing their dental anxiety. Methods. A nonrandomized, noninterventional, and anonymous, Qualtrics survey was administered prospectively to members of one local and one national organization. Results. Of the 107 respondents (response rate of 81.06%), 89% treat special needs patients. Positive reinforcement (88.64%), distraction (85.23%), and enhancing control (85.23%) were the modalities most used by these participants. Regarding treating this population, the average response regarding both confidence and wanting to learn more fell between disagree and agree at 2.92, while the average response regarding concern about safety fell between agree and strongly agree at 3.22. Level of specific expertize had the strongest influence on a provider's decision to treat, while reimbursement level had the least influence. Among participants who completed postdoctoral education, the average response for how well their education prepared them to manage patients with special needs was higher for their postdoctoral training compared to their dental school training, with pediatric dentists reporting the highest rate of preparation. No correlation was found between year of dental school graduation and how well they felt their education prepared them for treating this population. Significance level was set at 5%. Conclusion. Dental education can have a significant impact on dentists' knowledge, attitudes, beliefs, and confidence about treating those with developmental disabilities and managing their dental anxiety. Acknowledging that this relationship exists should encourage educational improvements in this area.